Activating Transitional Justice Mechanisms and Their Role in Achieving Civil Peace in Iraq (The Yazidi Component as a Model) - Salman, Jabbar (Journal of Legal Sciences, 2026)
With the In the pre-2003 era, Iraqi society suffered from authoritarian rule, political violence, gross violations, repression, and enforced disappearances. This created the need to establish effective legal and social measures to address the spillovers and repercussions of the past. This was embodied in the establishment of a group of institutions that took it upon themselves to address these residuals by implementing transitional justice mechanisms to achieve civil peace. Through these mechanisms, it was necessary to work to activate them politically to uncover the truth, enforce accountability, prevent impunity, and pursue institutional reform. Economically, it was necessary to compensate victims and their families. Culturally, culture played a prominent role in preserving civil peace through its connection to human memory, commemorating memories, and glorifying sacrifice through various initiatives.